Question and Answers Forum

Coordinate Geometry Questions

Question Number 209307 by efronzo1 last updated on 06/Jul/24

Commented by mr W last updated on 06/Jul/24

$$\mid{QR}\mid<\frac{\mathrm{8}}{\mathrm{3}}−\mathrm{1}=\frac{\mathrm{5}}{\mathrm{3}} \\$$$$\frac{{QR}}{{PR}}=\frac{\mathrm{2}}{\mathrm{1}}\:\Rightarrow\frac{{PQ}}{{QR}}=\frac{\sqrt{\mathrm{5}}}{\mathrm{2}} \\$$$$\mid{PQ}\mid=\frac{\sqrt{\mathrm{5}}}{\mathrm{2}}×{QR}<\frac{\sqrt{\mathrm{5}}}{\mathrm{2}}×\frac{\mathrm{5}}{\mathrm{3}}=\frac{\mathrm{5}\sqrt{\mathrm{5}}}{\mathrm{6}}<\sqrt{\mathrm{5}} \\$$$$\Rightarrow{impossible}\:{that}\:\mid{PQ}\mid=\sqrt{\mathrm{5}}\:! \\$$$$\Rightarrow{question}\:{is}\:{wrong}! \\$$

Commented by mr W last updated on 06/Jul/24

Commented by efronzo1 last updated on 07/Jul/24

$$\:\cancel{ } \\$$

Answered by A5T last updated on 07/Jul/24

$${For}\:{the}\:{corrected}\:{question}:\:{y}=\left(\frac{\mathrm{2}}{\mathrm{3}}\right)^{{x}+\mathrm{1}} +\frac{\mathrm{8}}{\mathrm{3}} \\$$$${P}\left({p}_{\mathrm{1}} ,{p}_{\mathrm{2}} \right),{Q}\left({q}_{\mathrm{1}} ,{q}_{\mathrm{2}} \right) \\$$$$\sqrt{\left({q}_{\mathrm{1}} −{p}_{\mathrm{1}} \right)^{\mathrm{2}} +\left({q}_{\mathrm{2}} −{p}_{\mathrm{2}} \right)^{\mathrm{2}} }=\sqrt{\mathrm{5}} \\$$$${y}−\mathrm{2}{x}={k}\Rightarrow{p}_{\mathrm{2}} −\mathrm{2}{p}_{\mathrm{1}} ={q}_{\mathrm{2}} −\mathrm{2}{q}_{\mathrm{1}} \\$$$$\Rightarrow\mathrm{2}\left({p}_{\mathrm{1}} −{q}_{\mathrm{1}} \right)={p}_{\mathrm{2}} −{q}_{\mathrm{2}} ...\left({i}\right) \\$$$$\Rightarrow\sqrt{\left({p}_{\mathrm{1}} −{q}_{\mathrm{1}} \right)^{\mathrm{2}} +\mathrm{4}\left({p}_{\mathrm{1}} −{q}_{\mathrm{1}} \right)^{\mathrm{2}} }=\sqrt{\mathrm{5}} \\$$$$\Rightarrow\mathrm{5}\left({p}_{\mathrm{1}} −{q}_{\mathrm{1}} \right)^{\mathrm{2}} =\mathrm{5}\Rightarrow\left({p}_{\mathrm{1}} −{q}_{\mathrm{1}} \right)=−\mathrm{1} \\$$$${p}_{\mathrm{2}} =\frac{\mathrm{2}^{{p}_{\mathrm{1}} +\mathrm{3}} }{\mathrm{3}^{{p}_{\mathrm{1}} +\mathrm{3}} }+\mathrm{1};\:{q}_{\mathrm{2}} =\frac{\mathrm{2}^{{q}_{\mathrm{1}} +\mathrm{1}} }{\mathrm{3}^{{q}_{\mathrm{1}} +\mathrm{1}} }+\frac{\mathrm{8}}{\mathrm{3}} \\$$$$\Rightarrow{p}_{\mathrm{2}} =\frac{\mathrm{2}^{{q}_{\mathrm{1}} } ×\mathrm{4}}{\mathrm{3}^{{q}_{\mathrm{1}} } ×\mathrm{9}}+\mathrm{1};\:{q}_{\mathrm{2}} =\frac{\mathrm{2}^{{q}_{\mathrm{1}} } ×\mathrm{2}}{\mathrm{3}^{{q}_{\mathrm{1}} } ×\mathrm{3}}+\frac{\mathrm{8}}{\mathrm{3}} \\$$$${p}_{\mathrm{2}} =\frac{\mathrm{2}{q}_{\mathrm{2}} }{\mathrm{3}}−\frac{\mathrm{7}}{\mathrm{9}}\Rightarrow{p}_{\mathrm{2}} −{q}_{\mathrm{2}} =\frac{−{q}_{\mathrm{2}} }{\mathrm{3}}−\frac{\mathrm{7}}{\mathrm{9}} \\$$$$\Rightarrow−\mathrm{2}+\frac{\mathrm{7}}{\mathrm{9}}=\frac{−\mathrm{11}}{\mathrm{9}}=\frac{−{q}_{\mathrm{2}} }{\mathrm{3}}\Rightarrow{q}_{\mathrm{2}} =\frac{\mathrm{11}}{\mathrm{3}}\Rightarrow{p}_{\mathrm{2}} =\frac{\mathrm{15}}{\mathrm{9}} \\$$$$\Rightarrow{q}_{\mathrm{1}} +\mathrm{1}=\mathrm{0}\Rightarrow{q}_{\mathrm{1}} =−\mathrm{1}\Rightarrow{p}_{\mathrm{1}} =−\mathrm{2} \\$$$$\Rightarrow{k}={p}_{\mathrm{2}} −\mathrm{2}{p}_{\mathrm{1}} =\frac{\mathrm{15}}{\mathrm{9}}+\mathrm{4}=\frac{\mathrm{17}}{\mathrm{3}} \\$$

Answered by mr W last updated on 07/Jul/24

$${y}_{\mathrm{1}} =\left(\frac{\mathrm{2}}{\mathrm{3}}\right)^{{x}_{\mathrm{1}} +\mathrm{3}} +\mathrm{1}=\mathrm{2}{x}_{\mathrm{1}} +{k}\:\:\:...\left({i}\right) \\$$$${y}_{\mathrm{2}} =\left(\frac{\mathrm{2}}{\mathrm{3}}\right)^{{x}_{\mathrm{1}} +\mathrm{1}} +\frac{\mathrm{8}}{\mathrm{3}}=\mathrm{2}{x}_{\mathrm{2}} +{k}\:\:\:...\left({ii}\right) \\$$$${PQ}=\sqrt{\mathrm{5}}\:\Rightarrow{x}_{\mathrm{2}} −{x}_{\mathrm{1}} =\mathrm{1} \\$$$$\left(\frac{\mathrm{2}}{\mathrm{3}}\right)^{{x}_{\mathrm{2}} +\mathrm{1}} +\frac{\mathrm{8}}{\mathrm{3}}−\left(\frac{\mathrm{2}}{\mathrm{3}}\right)^{{x}_{\mathrm{1}} +\mathrm{3}} −\mathrm{1}=\mathrm{2}\left({x}_{\mathrm{2}} −{x}_{\mathrm{1}} \right) \\$$$$\left[\left(\frac{\mathrm{2}}{\mathrm{3}}\right)^{{x}_{\mathrm{2}} −{x}_{\mathrm{1}} −\mathrm{2}} −\mathrm{1}\right]\left(\frac{\mathrm{2}}{\mathrm{3}}\right)^{{x}_{\mathrm{1}} +\mathrm{3}} =\frac{\mathrm{1}}{\mathrm{3}} \\$$$$\left[\left(\frac{\mathrm{2}}{\mathrm{3}}\right)^{−\mathrm{1}} −\mathrm{1}\right]\left(\frac{\mathrm{2}}{\mathrm{3}}\right)^{{x}_{\mathrm{1}} +\mathrm{3}} =\frac{\mathrm{1}}{\mathrm{3}} \\$$$$\left(\frac{\mathrm{2}}{\mathrm{3}}\right)^{{x}_{\mathrm{1}} +\mathrm{3}} =\frac{\mathrm{2}}{\mathrm{3}}\: \\$$$$\Rightarrow{x}_{\mathrm{1}} +\mathrm{3}=\mathrm{1}\:\Rightarrow{x}_{\mathrm{1}} =−\mathrm{2} \\$$$$\left(\frac{\mathrm{2}}{\mathrm{3}}\right)^{−\mathrm{2}+\mathrm{3}} +\mathrm{1}=\mathrm{2}\left(−\mathrm{2}\right)+{k}\:\Rightarrow{k}=\frac{\mathrm{17}}{\mathrm{3}}\:\:\checkmark \\$$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com